Il corpo-oggetto nell'opera filmica di Paolo Gioli (Mantichora. Italian Journal of Performance Studies, 2026)
The relationship that Paolo Gioli establishes between his artistic production and the body is the cornerstone of his creative research. This connection, combined with a subversive use of photographic and filmic apparatuses, allows him to emerge as a peculiar figure within the contemporary artistic landscape. The experimentation carried out by the visual artist advances a deeply incisive approach to the body and, opening up to the most diverse possibilities of manipulation, draws it into a regressive path that forces it into a new identity: that of a “body-object”.